2022
DOI: 10.3390/v14010147
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Attenuates Eosinophilic Inflammation but Is Not Essential for Protection against RSV-Enhanced Asthmatic Comorbidity in Adult Mice

Abstract: The susceptibility to respiratory syncytial virus (RSV) infection in early life has been associated with a deficient T-helper cell type 1 (Th1) response. Conversely, healthy adults generally do not exhibit severe illness from RSV infection. In the current study, we investigated whether Th1 cytokine IFN-γ is essential for protection against RSV and RSV-associated comorbidities in adult mice. We found that, distinct from influenza virus, prior RSV infection does not induce significant IFN-γ production and suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
2
0
2
Order By: Relevance
“…Our findings suggest that the degree of IFN-γ reduction depends on the severity of asthma. Our data are in line with the results of other researchers who have demonstrated reduced levels of IFN-γ in frequently ill children [24] and in mice with asthma [14,15,23]. In their work, they show how the levels of IFN-γ change under the influence of medicines, which leads to an improvement in the clinical and laboratory parameters of patients with asthma.…”
Section: педіатрія / Pediatricssupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings suggest that the degree of IFN-γ reduction depends on the severity of asthma. Our data are in line with the results of other researchers who have demonstrated reduced levels of IFN-γ in frequently ill children [24] and in mice with asthma [14,15,23]. In their work, they show how the levels of IFN-γ change under the influence of medicines, which leads to an improvement in the clinical and laboratory parameters of patients with asthma.…”
Section: педіатрія / Pediatricssupporting
confidence: 92%
“…Researchers have also shown that elevated levels of IL-2 are associated with both acute and chronic respiratory tract pathologies [23].…”
Section: педіатрія / Pediatricsmentioning
confidence: 99%
“…In one report, type 1 cytokines including IL-6, IL-1β, and interferon-gamma (IFN- γ ) levels were systemically elevated in SARS-CoV-2 infected patients ( 9 ). IFN- γ is also known to attenuate respiratory eosinophilic inflammation ( 17 ). These findings suggest that SARS-CoV-2 infection may have contributed to the relief of ECRS.…”
Section: Discussionmentioning
confidence: 99%
“…Існують наукові роботи, які показують зниження рівнів γ-інтерферону у дітей, що часто хворіють [33]. Доведено, що зниження рівнів γ-інтерферону відповідало еозінофільному типу запалення у дорослих мишей з астмою [34]. Виявлені в нашій роботі знижені рівні γ-інтерферону в пацієнтів з wheezing, не пов'язаного з вірусними тригерами.…”
Section: показникиunclassified
“…При цьому статистично достовірними були виявлені зв'язки у пацієнтів з лікар-діагностованою астмою. Подібні зв'язки були продемонстровані в сучасних наукових роботах при вивченні хронічного запалення при астмі у мишей [27,34]. Дане дослідження підтверджує вірогідний зворотній зв'язок у дітей з хронічним алергійним запаленням.…”
Section: показникиunclassified